Pengaruh pemberian prostaglandin Fla (PGF2a) terhadap kualitas semen dan kadar testosteron domba lokal=The Effect of prostaglandin Fla (PGF2a) on The Semen Quality and The Testosterone Level in The Local Ram - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
ABSTRACT The study was conducted to evaluate the effect of PGF2a administration on the quality of semen and the testosterone level in the local ram. Four rams of two year old were use in this study. Semen and blood collection were performed 4 times by one week interval, i.e. one week before the first administration of PGF2a